Technology and agricultural development in pre-war Japan - Francks, Penelope
There was little or no detailed planning involved; schemes were often formulated as problems arose. At Tomioka, the government’s premier silk reeling facility, for example, no one even considered who would work there. This lack of planning and foresight was typical of early Japanese efforts at technology transfer and industrial development.